Analisis Du Pont System Pada Perusahaan Sektor Tekstil Yang Terdaftar Di Issi Periode 2017-2022 - Diani Nabila Putri; M. Edman Syarief; Ine Mayasari (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The research aimed to analyze the financial performance of Textile Sector companies that are consistent in ISSI for the period 2017-2022 using the Du Pont System method. This Du Pont analysis is performed to see what factors can affect the increase and decrease in company profitability by looking at existing ratios. Du Pont uses five ratios which are, Net Profit Margin, Total Asset Turnover, Return on Investment, Equity Multiplier and Return on Equity. The researched method employed is a quantitative descriptive analysis. The sample of data used has been selected with purposive sampling method and resulted in 3 consistent companies listed on ISSI during 2017-2022. The results showed that PT Indo Rama Syntetics had relatively good Du Pont ROE performance and was already above the average textile sector industry compared to two other companies, namely PT Tifico Fiber Indonesia and PT Trisula international. Keywords: Du Pont System, Financial Performance